Participative management theory and feminist leadership styles - Maslina Mohammed Shaed (Penerbit Universiti Kebangsaan Malaysia, 2018)
Globalization has completely changed the world and brings huge impacts towards the organization. Therefore, to survive and compete in this challenging world, most of the organizations have transformed from traditional management styles to more effective and adaptive management styles. Hence, participative management has emerged as a modern management style, which is less hierarchical, applies a bottom-up approach, and focuses on consensus or consultative decision-making. This management style emphasizes on employee participation in the decision-making (PDM) process of an organization. However, the implementation of participative management also depends on leadership styles practiced by a leader. Thus, feminist leadership styles such as people-oriented, nurturing, participative, democratic and transformative have seemed to be more associated and more supportive towards participative management as compared to traditional leadership styles or masculine leadership styles (control-wise, autocratic, top-down approach and coercive) . This study examined the association between participative management and feminist leadership styles based on the review of past literature. The conceptual findings revealed that the participative management theory had similar characteristics and association with feminist leadership styles. It can be concluded that feminist leadership styles can bring successfulness to the implementation of participative management in the organization and enhance the level of employee participation in decision-making (PDM).